On the Use of Steel and Aluminum Materials for Frame Structure of Electric Trike - Samuel Rahardian; Ilyasa Dwi Putra; Bentang Arief Budiman (Faculty of Engineering and Technology, Sampoerna University, 2021)
This work investigated the pros and cons of aluminum material used for electric trike frame compared with steel material. With a compact design and small dimension, e-trike is suitable to be used in many relatively small road accesses. However, the compact design can cause the frame to receive high and concentrated stress. The aluminum-based frame had lower strength, but lighter weight compared to the steel-based frame. In this study, the stress evaluation for both aluminum-based and steel-based frames is done using the finite element method. The minimum thickness of the aluminum-based frame was iterated to match the strength of the steel-based frame. The results showed that the aluminum-based frame has comparable performance to the steel-based frame but with lighter weight. However, the production cost of the aluminum-based frame might be a challenging issue to be solved.